Amino‐polyvinyl Alcohol Coated Superparamagnetic Iron Oxide Nanoparticles are Suitable for Monitoring of Human Mesenchymal Stromal Cells In Vivo. Issue 21 (2nd July 2014) - Schulze, Frank; Dienelt, Anke; Geissler, Sven; Zaslansky, Paul; Schoon, Janosch; Henzler, Katja; Guttmann, Peter; Gramoun, Azza; Crowe, Lindsey A.; Maurizi, Lionel; Vallée, Jean‐Paul; Hofmann, Heinrich; et al.
<x xml:space="preserve">Abstract</x> Mesenchymal stromal cells (MSCs) are promising candidates in regenerative cell‐therapies. However, optimizing their number and route of delivery remains a critical issue, which can be addressed by monitoring the MSCs' bio‐distribution in vivo using super‐paramagnetic iron‐oxide nanoparticles (SPIONs). In this study, amino‐polyvinyl alcohol coated (A‐PVA) SPIONs are introduced for cell‐labeling and visualization by magnetic resonance imaging (MRI) of human MSCs. Size and surface charge of A‐PVA‐SPIONs differ depending on their solvent. Under MSC‐labeling conditions, A‐PVA‐SPIONs have a hydrodynamic diameter of 42 ± 2 nm and a negative Zeta potential of 25 ± 5 mV, which enable efficient internalization by MSCs without the need to use transfection agents. Transmission X‐ray microscopy localizes A‐PVA‐SPIONs in intracellular vesicles and as cytosolic single particles. After identifying non‐interfering cell‐assays and determining the delivered and cellular dose, in addition to the administered dose, A‐PVA‐SPIONs are found to be non‐toxic to MSCs and non‐destructive towards their multi‐lineage differentiation potential. Surprisingly, MSC migration is increased. In MRI, A‐PVA‐SPION‐labeled MSCs are successfully visualized in vitro and in vivo. In conclusion, A‐PVA‐SPIONs have no unfavorable influences on MSCs, although it becomes evident how sensitive their functional behavior is towards SPION‐labeling. And A‐PVA‐SPIONs allow MSC‐monitoring in vivo.